2015
DOI: 10.1021/acs.molpharmaceut.5b00402
|View full text |Cite
|
Sign up to set email alerts
|

Brain Targeting of a Water Insoluble Antipsychotic Drug Haloperidol via the Intranasal Route Using PAMAM Dendrimer

Abstract: Delivery of therapeutics to the brain is challenging because many organic molecules have inadequate aqueous solubility and limited bioavailability. We investigated the efficiency of a dendrimer-based formulation of a poorly aqueous soluble drug, haloperidol, in targeting the brain via intranasal and intraperitoneal administration. Aqueous solubility of haloperidol was increased by more than 100-fold in the developed formulation. Formulation was assessed via different routes of administration for behavioral (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…The results of the reduced brain infraction volume were a proof for the activity of siRNA dendrimers as an efficient knock-down of HMGB [212]. In another study, the PAMAM formulation of haloperidol intended for brain targeting showed 100-fold higher solubility with significant brain and plasma concentrations, resulting in a 6.7-fold smaller dose being required to produce a response similar to the intraperitoneal (IP) injection [220]. Additionally, PAMAM showed substantial effects on the nasal absorption of poorly absorbed molecules, namely calcitonin, insulin, and fluorescein isothiocyanate-labelled dextran, as it was pointed out via in vivo studies using a rat model [221].…”
Section: Dendrimersmentioning
confidence: 95%
“…The results of the reduced brain infraction volume were a proof for the activity of siRNA dendrimers as an efficient knock-down of HMGB [212]. In another study, the PAMAM formulation of haloperidol intended for brain targeting showed 100-fold higher solubility with significant brain and plasma concentrations, resulting in a 6.7-fold smaller dose being required to produce a response similar to the intraperitoneal (IP) injection [220]. Additionally, PAMAM showed substantial effects on the nasal absorption of poorly absorbed molecules, namely calcitonin, insulin, and fluorescein isothiocyanate-labelled dextran, as it was pointed out via in vivo studies using a rat model [221].…”
Section: Dendrimersmentioning
confidence: 95%
“…Furthermore, dendrimers have more efficient paracellular and transcellular transport across the BBB, which makes them ideal carriers for targeting water-insoluble drugs to the brain [122]. Katare et al [123] investigated the efficiency of water-insoluble antipsychotic drug haloperidol via the intranasal route using the PAMAM dendrimer. They demonstrated that the aqueous solubility of haloperidol was increased with the dendrimer-based formulation and showed a significantly higher distribution of haloperidol in the brain and plasma compared to a control formulation of the drug.…”
Section: Dendrimers In Central Nervous Systems (Cns) Drug Deliverymentioning
confidence: 99%
“…Additionally, 6.7 times lower doses of the dendrimer鈭抙aloperidol formulation administered via the intranasal route produced behavioral responses that were comparable to those induced by haloperidol formulations administered via intraperitoneal injection. This study demonstrates the potential of dendrimer in improving the delivery of water insoluble drugs to brain 39 .…”
Section: Dendrimers In Cns Drug Deliverymentioning
confidence: 65%